A catalyst for synthesizing methanol and a preparation method and application thereof

CN122999207APending Publication Date: 2026-10-30BAZHONG XINHONG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610944557.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有单一稀土氧化物掺杂虽然能够改善其中一个反应环节,但难以同时建立二氧化碳活化位、活性相稳定界面和甲醇选择性调节位;

Benefits of technology

1、 通过在CuO-ZnO-Al2O3基体中引入铈锆镧复合氧化物,使二氧化碳活化、铜基活性相稳定和甲醇选择性调节在同一界面活性区内承接,从而缓解转化率、甲醇选择性和CO副产物抑制难以同步兼顾的问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999207A_ABST
    Figure CN122999207A_ABST
Patent Text Reader

Abstract

The application discloses a kind of catalyst for synthesizing methanol and its preparation method and application, specifically related to carbon dioxide resource utilization and catalyst preparation field, including configuration Cu, Zn, Al, Ce, Zr, La nitrate precursor according to metal element mole ratio, by Na2CO3 concurrent co-precipitation, aging, drying, calcination and H2 Atmosphere reduction, form the catalyst containing copper-based active phase and cerium zirconium lanthanum composite oxide interface active area, and be used for fixed bed CO2 Hydrogenation methanol reaction.By introducing the cerium zirconium lanthanum composite oxide containing CeO2 and La2O3 rare earth oxide in CuO-ZnO-Al2O3 matrix, carbon dioxide activation, copper-based active phase stability and methanol selectivity regulation are accepted in the same interface active area, so as to alleviate the problem that conversion rate, methanol selectivity and CO byproduct inhibition are difficult to consider simultaneously.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon dioxide resource utilization and catalyst preparation technology, and more specifically, to a catalyst for the synthesis of methanol, its preparation method, and its application. Background Technology

[0002] The industrial catalytic system for the hydrogenation of carbon dioxide to methanol typically uses Cu-Zn-Al oxide catalysts as the core of the reaction. The activation of hydrogen and the hydrogenation of carbon-containing intermediates are completed through a copper-based active phase, and the dispersion of copper species and the stability of the catalyst framework are maintained by zinc and aluminum oxides, which are used to convert carbon dioxide into methanol. In the continuous operation scenario of a fixed-bed reactor, the reaction system needs to simultaneously achieve high carbon dioxide conversion, high methanol selectivity, and low CO byproduct ratio under the constraints of 270℃, 8.0MPa, and H2 / CO2 molar ratio of 5.1. However, the mainstream Cu-Zn-Al catalyst mainly relies on the copper-zinc interface to complete the hydrogenation conversion within this reaction window, lacking synchronous regulation of carbon dioxide adsorption and activation, copper-based active phase anti-migration, and surface acidity and alkalinity distribution. The operating results show that the residual carbon dioxide in the outlet gas is still high, the methanol selectivity decreases due to competition from the reverse water-gas shift path, and the CO byproduct ratio increases. While existing single rare earth oxide doping can improve one of the reaction steps, it is difficult to simultaneously establish carbon dioxide activation sites, active phase stable interfaces, and methanol selectivity adjustment sites. The technical problem to be solved by this application is: how to construct a composite oxide catalytic structure in the Cu-Zn-Al catalytic system that can simultaneously regulate carbon dioxide adsorption and activation, copper-based active phase stabilization and methanol generation pathway, so as to alleviate the problem that it is difficult to simultaneously achieve conversion rate, methanol selectivity and CO by-product inhibition in the fixed-bed carbon dioxide hydrogenation to methanol process. Summary of the Invention

[0003] To overcome the aforementioned deficiencies of the prior art, embodiments of the present invention provide a catalyst for the synthesis of methanol, its preparation method, and its application. This is achieved by in-situ introducing a cerium-zirconium-lanthanum composite oxide composed of rare earth oxides CeO2, ZrO2, and La2O3 into a CuO-ZnO-Al2O3 matrix. Through co-precipitation, calcination, and reduction under H2 atmosphere, an interfacial active region is formed where a copper-based active phase connects to the cerium-zirconium-lanthanum composite oxide. This allows carbon dioxide adsorption activation, hydrogenation conversion of carbon-containing intermediates, stabilization of the copper-based active phase, and methanol selectivity adjustment to synergistically occur within the same catalyst structure, thereby solving the problems mentioned in the background art.

[0004] To achieve the above objectives, the present invention provides the following technical solution: a catalyst for synthesizing methanol, comprising: a catalyst for the hydrogenation of carbon dioxide to methanol, the catalyst comprising a CuO-ZnO-Al2O3 matrix and a cerium-zirconium-lanthanum composite oxide dispersed in the CuO-ZnO-Al2O3 matrix; the cerium-zirconium-lanthanum composite oxide comprising CeO2, ZrO2 and La2O3; Based on the molar amounts of metal elements, the molar ratio of Cu, Zn, Al, Ce, Zr, and La is (30-40):(20-30):(10-15):(5-8):(3-5):(1-3). After reduction in an H2 atmosphere, a copper-based active phase is formed in the CuO-ZnO-Al2O3 matrix, and an interfacial active region is formed between the cerium-zirconium-lanthanum composite oxide and the copper-based active phase for carbon dioxide adsorption activation, hydrogenation conversion of carbon-containing intermediates, and selective adjustment of methanol.

[0005] In a preferred embodiment, the molar ratio of Cu, Zn, Al, Ce, Zr, and La is 35:25:12:6:4:2, and the molar ratio of Ce, Zr, and La is 3:2:1, based on the molar amounts of the metal elements.

[0006] In a preferred embodiment, the cerium-zirconium-lanthanum composite oxide is formed by co-incorporating Ce(NO3)3, ZrO(NO3)2 and La(NO3)3 with Cu(NO3)2, Zn(NO3)2 and Al(NO3)3 in the same mixed nitrate solution, and then co-precipitating and calcining it in the presence of Na2CO3 solution. CeO2, ZrO2 and La2O3 are all in-situ formed oxide dispersions. Based on the molar parts of metallic elements, Ce is 5-8 parts, Zr is 3-5 parts, and La is 1-3 parts; CeO2 is used to form carbon dioxide adsorption activation sites, ZrO2 is used to form a copper-based active phase stable interface, and La2O3 is used to form surface acidity and alkalinity adjustment sites, so that the cerium-zirconium-lanthanum composite oxides are configured into composite control units according to the functional division of carbon dioxide adsorption activation, copper-based active phase stabilization and methanol selective regulation.

[0007] In a preferred embodiment, the interfacial active region is a composite region formed by drying, calcining and reducing the same precipitated particles in an H2 atmosphere. The composite region simultaneously includes a copper-based active phase formed by reducing CuO in an H2 atmosphere, a zinc-aluminum oxide framework formed by ZnO and Al2O3, and a cerium-zirconium-lanthanum composite oxide formed by CeO2, ZrO2 and La2O3. Within the interfacial active region, the CeO2 region serves as the carbon dioxide adsorption activation region, the copper-based active phase region serves as the carbon-containing intermediate hydrogenation conversion region, the ZrO2 region serves as the copper-based active phase migration restriction region, and the La2O3 region serves as the surface acidity / alkalinity adjustment region. The carbon dioxide adsorption activation region, the carbon-containing intermediate hydrogenation conversion region, the copper-based active phase migration restriction region, and the surface acidity / alkalinity adjustment region are all supported by composite precursor particles formed by co-precipitation.

[0008] A method for preparing a catalyst for methanol synthesis, comprising: S1. Prepare a mixed nitrate solution containing Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Ce(NO3)3, ZrO(NO3)2 and La(NO3)3 according to the molar ratio of Cu, Zn, Al, Ce, Zr and La as (30-40):(20-30):(10-15):(5-8):(3-5):(1-3); S2. The mixed nitrate solution and Na2CO3 solution are added dropwise into the reactor in a co-current manner. Co-precipitation is carried out under the conditions of pH 7-8 and liquid phase temperature of 60-70℃ in the reactor to obtain a precipitate slurry containing Cu, Zn, Al, Ce, Zr and La precursors. S3. After aging the precipitated slurry for 12 hours, filter and wash it to obtain the composite precursor filter cake. S4. The composite precursor filter cake is dried at 110°C and then calcined at 500°C for 4 hours to obtain the oxidized catalyst precursor. S5. The oxidized catalyst precursor is reduced in H2 atmosphere at 300℃ for 2h to obtain the catalyst for methanol synthesis.

[0009] In a preferred embodiment, in S2, the mixed nitrate solution and Na2CO3 solution are added to the reactor in a co-current manner. The pH of the liquid phase in the reactor is maintained at 7.5, and the temperature of the liquid phase in the reactor is maintained at 65°C, so that the precursors of Cu, Zn, Al, Ce, Zr, and La are generated simultaneously in the same liquid phase environment and enter the same precipitate slurry.

[0010] In a preferred embodiment, in S3, the precipitated slurry is aged for 12 hours to allow the matrix precursor containing Cu, Zn, and Al and the composite oxide precursor containing Ce, Zr, and La to rearrange and distribute within the same precipitate particles; after washing to remove water-soluble sodium salts and nitrates from the precipitated slurry, a composite precursor filter cake is obtained.

[0011] In a preferred embodiment, in S4 and S5, calcination at 500°C is used to convert the composite precursor filter cake into an oxidized catalyst precursor containing a CuO-ZnO-Al2O3 matrix and CeO2, ZrO2, and La2O3 composite oxides, and reduction at 300°C in an H2 atmosphere is used to reduce CuO to form a copper-based active phase and retain the cerium-zirconium-lanthanum composite oxide around the copper-based active phase.

[0012] An application of a catalyst for methanol synthesis is characterized in that the catalyst is used in a fixed-bed reactor for the hydrogenation of carbon dioxide to methanol reaction, the reaction feedstocks include H2 and CO2, the molar ratio of H2 to CO2 is 5.1, the reaction system is at 270°C, and the reaction pressure is 6.0-8.0 MPa.

[0013] In a preferred embodiment, the fixed-bed reactor has a reaction pressure of 6.0 MPa and a reaction space velocity of 5000 h⁻¹. -1 The reaction system was set at 270℃, with a molar ratio of H2 to CO2 of 5.1 and a reaction space velocity of 5000 h⁻¹. -1 Under these conditions, the carbon dioxide conversion rate was 97.2%, the methanol selectivity was 94.1%, and the CO selectivity was 3.5%.

[0014] The technical effects and advantages of this invention are as follows: 1. By introducing cerium-zirconium-lanthanum composite oxides into the CuO-ZnO-Al2O3 matrix, carbon dioxide activation, copper-based active phase stabilization, and methanol selectivity regulation can be achieved within the same interfacial active region, thereby alleviating the problem of simultaneously achieving conversion rate, methanol selectivity, and CO byproduct inhibition. 2. By limiting the molar ratio of metal elements Cu, Zn, Al, Ce, Zr, and La, the matrix components and cerium, zirconium, and lanthanum control components are in a controlled ratio relationship, avoiding excessive obscuring of the active region by a single component, thereby improving the stability of the catalyst composition within a certain range. 3. By co-precipitating Ce, Zr, and La precursors with Cu, Zn, and Al precursors into a mixed nitrate solution and then co-precipitating them in a co-current manner, CeO2, ZrO2, and La2O3 are dispersed in situ, thereby relatively improving the contact relationship between the composite oxide and the copper-based active phase. 4. Through continuous treatment of aging, air roasting and H2 atmosphere reduction, the composite precursor filter cake is transformed into an oxidized catalyst precursor, and CuO is formed into a copper-based active phase, thereby establishing an interfacial active region between the copper-based active phase and the cerium-zirconium-lanthanum composite oxide. 5. By directly switching the mixed feed gas of H2 and CO2 after reduction in the H2 atmosphere in the fixed-bed reactor, the formation process of the copper-based active phase is connected with the carbon dioxide hydrogenation reaction process, thereby relatively reducing the interference of the transfer of the reduced catalyst on the reaction state. Attached Figure Description

[0015] Figure 1 This is a flowchart of the present invention. Detailed Implementation

[0016] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0017] Refer to the instruction manual appendix Figure 1 The present invention discloses a catalyst for synthesizing methanol, a method for preparing the same, and its application, comprising the following common implementation conditions: In the following examples and comparative examples, the amounts of Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Ce(NO3)3, ZrO(NO3)2, and La(NO3)3 added are all calculated based on the molar amounts of Cu, Zn, Al, Ce, Zr, and La metal elements contained therein; when the nitrate raw material is a hydrate, the mass of the added material is calculated based on the amount of water of crystallization in the hydrate molecular formula; ZrO(NO3)2 is added to the mixed nitrate solution based on the molar amount of Zr element therein, and when ZrO(NO3)2 is added in the form of an aqueous solution, the volume added is calculated based on the Zr element content in the material; In the following examples and comparative examples, the reaction space velocity is the gas volume space velocity, calculated as the ratio of the sum of the inlet volumetric flow rates of H2 and CO2 at 0°C and 101.325 kPa to the catalyst bed volume, in h. -1 The molar ratio of H2 to CO2 is the ratio of the molar flow rate of H2 to the molar flow rate of CO2 at the inlet of the fixed-bed reactor; the reaction system temperature of 270℃ refers to the temperature of the catalyst bed measurement point in the fixed-bed reactor at 270℃; the reaction pressure is the bed operating pressure maintained by the back pressure valve at the outlet of the fixed-bed reactor. The product from the fixed-bed reactor flows through a condensation unit. The condensate is used for quantitative analysis of methanol, and the uncondensed gas is used for quantitative analysis of CO2, CO, and unreacted H2. The product separation at the outlet is only used for catalytic performance testing and is not used as a methanol refining step. CO2 and CO are quantified by gas chromatography, and methanol in the condensate is quantified by gas chromatography. Quantitative curves are established using standard gases and methanol standard solutions before detection. The carbon dioxide conversion rate is calculated by dividing the difference between the inlet CO2 molar flow rate and the outlet unreacted CO2 molar flow rate of the fixed-bed reactor by the inlet CO2 molar flow rate of the fixed-bed reactor, and then multiplying by 100%. The difference between the inlet CO2 molar flow rate and the outlet unreacted CO2 molar flow rate of the fixed-bed reactor represents the CO2 molar flow rate that participates in the reaction. Methanol selectivity is calculated by dividing the molar flow rate of methanol in the product at the outlet of the fixed-bed reactor by the molar flow rate of CO2 participating in the reaction, and then multiplying by 100%. The molar flow rate of CO2 participating in the reaction is the difference between the molar flow rate of CO2 at the inlet of the fixed-bed reactor and the molar flow rate of unreacted CO2 at the outlet of the fixed-bed reactor. CO selectivity is calculated by dividing the CO molar flow rate at the outlet of the fixed-bed reactor by the molar flow rate of CO2 participating in the reaction, and then multiplying by 100%. The molar flow rate of CO2 participating in the reaction is the difference between the molar flow rate of CO2 at the inlet of the fixed-bed reactor and the molar flow rate of unreacted CO2 at the outlet of the fixed-bed reactor.

[0018] Example 1 A mixed nitrate solution was prepared based on the molar amounts of metal elements, with the molar ratio of Cu, Zn, Al, Ce, Zr, and La being 35:25:12:6:4:2. Specifically, Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Ce(NO3)3, ZrO(NO3)2, and La(NO3)3 were converted to the molar amounts of Cu (0.35 mol), Zn (0.25 mol), Al (0.12 mol), Ce (0.06 mol), Zr (0.04 mol), and La (0.02 mol) respectively, and then added to deionized water to prepare a mixed nitrate solution with a total molar concentration of 0.50 mol / L. Separately, Na2CO3 was added to deionized water to prepare a Na2CO3 solution with a concentration of 1.00 mol / L. Deionized water was added to the reactor as the base liquid, and stirring was started at 500 r / min to maintain the liquid phase in the reactor at 65°C. The mixed nitrate solution was added to the reactor at a constant flow rate, and the Na2CO3 solution was added to the reactor simultaneously. The flow rate of the Na2CO3 solution was adjusted according to the pH of the liquid phase in the reactor to maintain the pH of the liquid phase in the reactor at 7.5. After all the mixed nitrate solution was added, Na2CO3 solution was added to maintain the pH of the liquid phase in the reactor at 7.5 for 30 min to obtain a precipitate slurry containing Cu, Zn, Al, Ce, Zr, and La precursors. The precipitated slurry was aged in the mother liquor for 12 hours, during which the liquid phase in the reactor was maintained at 65°C. After aging, the mixture was filtered to obtain an aqueous composite precursor filter cake. The composite precursor filter cake was washed five times with deionized water, each time using three times the mass of the composite precursor filter cake, to remove water-soluble sodium salts and nitrates from the precipitated slurry. The washed composite precursor filter cake was dried at 110°C for 12 hours to obtain a dried precursor. The dried precursor was placed in an air atmosphere and heated to 500°C from an indoor environment at a rate of 3°C / min. It was then held at 500°C for 4 hours to obtain an oxidized catalyst precursor. The oxidized catalyst precursor comprised a CuO-ZnO-Al2O3 matrix and a cerium-zirconium-lanthanum composite oxide dispersed in the CuO-ZnO-Al2O3 matrix. The cerium-zirconium-lanthanum composite oxide included CeO2, ZrO2, and La2O3. CeO2, ZrO2, and La2O3 were formed by co-precipitating Ce(NO3)3, ZrO(NO3)2, and La(NO3)3 with Cu(NO3)2, Zn(NO3)2, and Al(NO3)3 in the same mixed nitrate solution, followed by co-precipitation and calcination under the action of Na2CO3 solution. The oxidized catalyst precursor was tableted, crushed, and sieved. 1.0 g of 20-40 mesh particles was loaded into a fixed-bed reactor. An H2 gas flow rate of 80 mL / min was introduced, and the temperature was raised from the indoor environment to 300°C at a rate of 3°C / min. The reactor was then reduced at 300°C in an H2 atmosphere for 2 h to obtain the catalyst for methanol synthesis. After reduction in an H2 atmosphere, a copper-based active phase was formed in the CuO-ZnO-Al2O3 matrix, and the cerium-zirconium-lanthanum composite oxide was retained around the copper-based active phase. An interfacial active region was formed between the cerium-zirconium-lanthanum composite oxide and the copper-based active phase. After the H2 atmosphere reduction was completed, the fixed-bed reactor was switched to a mixed feed gas of H2 and CO2, with a molar ratio of H2 to CO2 of 5.1. The reaction system was maintained at 270°C, a reaction pressure of 6.0 MPa, and a reaction space velocity of 5000 h⁻¹. -1 After the fixed-bed reactor outlet composition reached a stable state, the conversion rate and selectivity were calculated according to the product separation, gas chromatography quantification, and calculation methods in the common implementation conditions. The results showed that the carbon dioxide conversion rate was 97.2%, the methanol selectivity was 94.1%, and the CO selectivity was 3.5%. In this embodiment, the molar ratio of Ce, Zr, and La is 3:2:1; the CeO2 region serves as the carbon dioxide adsorption activation region, the copper-based active phase region serves as the hydrogenation conversion region of the carbon-containing intermediate, the ZrO2 region serves as the migration restriction region of the copper-based active phase, and the La2O3 region serves as the surface acidity / alkalinity adjustment region; the above regions are supported by composite precursor particles formed by co-precipitation, which are dried, calcined, and reduced in an H2 atmosphere to form the interfacial active region; In this embodiment, the H2 atmosphere reduction is carried out in a fixed-bed reactor. After the reduction is completed, the process is directly switched to a mixed feed gas of H2 and CO2 to avoid the copper-based active phase coming into contact with the external environment during the transfer process. This operation chain enables a continuous preparation and reaction process between the oxidized catalyst precursor, the copper-based active phase, the interfacial active zone, and the fixed-bed carbon dioxide hydrogenation to methanol reaction. Example 2 A mixed nitrate solution was prepared based on the molar amounts of metal elements, with the molar ratio of Cu, Zn, Al, Ce, Zr, and La being 30:30:15:5:3:1. Specifically, Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Ce(NO3)3, ZrO(NO3)2, and La(NO3)3 were converted to the molar amounts of Cu (0.30 mol), Zn (0.30 mol), Al (0.15 mol), Ce (0.05 mol), Zr (0.03 mol), and La (0.01 mol) respectively, and then added to deionized water to prepare a mixed nitrate solution with a total molar concentration of 0.30 mol / L. Separately, Na2CO3 was added to deionized water to prepare a Na2CO3 solution with a concentration of 0.80 mol / L. Deionized water was added to the reactor as the base liquid, and stirring was started at a speed of 400 r / min to maintain the liquid phase in the reactor at 60°C. The mixed nitrate solution was added to the reactor at a constant flow rate, and the Na2CO3 solution was added to the reactor simultaneously. The flow rate of the Na2CO3 solution was adjusted according to the pH of the liquid phase in the reactor to maintain the pH of the liquid phase in the reactor at 7.0. After all the mixed nitrate solution was added, Na2CO3 solution was added to maintain the pH of the liquid phase in the reactor at 7.0 for 30 min to obtain a precipitate slurry containing Cu, Zn, Al, Ce, Zr, and La precursors. The precipitated slurry was aged in the mother liquor for 12 hours, during which the liquid phase in the reactor was maintained at 60°C. After aging, the mixture was filtered to obtain an aqueous composite precursor filter cake. The composite precursor filter cake was washed five times with deionized water, each time using three times the mass of the composite precursor filter cake, to remove water-soluble sodium salts and nitrates from the precipitated slurry. The washed composite precursor filter cake was dried at 110°C for 12 hours to obtain a dried precursor. The dried precursor was placed in an air atmosphere and heated from an indoor environment to 500°C at a rate of 3°C / min. It was maintained at 500°C for 4 hours to obtain an oxidized catalyst precursor. The oxidized catalyst precursor was then tableted, crushed, and sieved. 1.0 g of 20-40 mesh particles was loaded into a fixed-bed reactor. An H2 gas flow rate of 80 mL / min was introduced, and the temperature was heated from an indoor environment to 300°C at a rate of 3°C / min. The reactor was then reduced in an H2 atmosphere at 300°C for 2 hours to obtain the catalyst for methanol synthesis. After reduction in an H2 atmosphere, the fixed-bed reactor was switched to a mixed feed gas of H2 and CO2, with a molar ratio of H2 to CO2 of 5.1. The reaction system was maintained at 270°C, a reaction pressure of 6.0 MPa, and a reaction space velocity of 5000 h⁻¹. -1 After the exported product flows through the condensation unit, the condensate and uncondensed gas enter the quantitative analysis step respectively. The carbon dioxide conversion rate, methanol selectivity and CO selectivity are obtained according to the calculation method in the common implementation conditions. In this embodiment, the molar ratio of Cu, Zn, Al, Ce, Zr, and La is on one side of the formulation range, still forming a CuO-ZnO-Al2O3 matrix and a cerium-zirconium-lanthanum composite oxide dispersed in the CuO-ZnO-Al2O3 matrix; CeO2, ZrO2, and La2O3 are all formed by calcining the precursors in the same precipitate slurry, without using the method of adding oxide powder later; In this embodiment, the liquid phase in the reactor is 60°C and pH is 7.0. Na2CO3 solution is still added as pH adjustment solution in parallel with the mixed nitrate solution. The precipitation endpoint is determined by the addition of all mixed nitrate solution, the maintenance of pH in the liquid phase in the reactor, and the subsequent holding for 30 minutes, so that Cu, Zn, Al, Ce, Zr, and La precursors are generated simultaneously and enter the same precipitation slurry. Example 3 A mixed nitrate solution was prepared based on the molar amounts of metal elements, with the molar ratio of Cu, Zn, Al, Ce, Zr, and La being 40:20:10:8:5:3. Specifically, Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Ce(NO3)3, ZrO(NO3)2, and La(NO3)3 were converted to the molar amounts of Cu (0.40 mol), Zn (0.20 mol), Al (0.10 mol), Ce (0.08 mol), Zr (0.05 mol), and La (0.03 mol) respectively, and then added to deionized water to prepare a mixed nitrate solution with a total molar concentration of 1.00 mol / L. Separately, Na2CO3 was added to deionized water to prepare a Na2CO3 solution with a concentration of 1.50 mol / L. Deionized water was added to the reactor as the base liquid, and stirring was started at 600 r / min to maintain the liquid phase in the reactor at 70°C. The mixed nitrate solution was added to the reactor at a constant flow rate, and the Na2CO3 solution was added to the reactor simultaneously. The flow rate of the Na2CO3 solution was adjusted according to the pH of the liquid phase in the reactor to maintain the pH of the liquid phase in the reactor at 8.0. After all the mixed nitrate solution was added, Na2CO3 solution was added to maintain the pH of the liquid phase in the reactor at 8.0 for 30 min, resulting in a precipitate slurry containing Cu, Zn, Al, Ce, Zr, and La precursors. The precipitated slurry was aged in the mother liquor for 12 hours, during which the liquid phase in the reactor was maintained at 70°C. After aging, the mixture was filtered to obtain an aqueous composite precursor filter cake. The composite precursor filter cake was washed five times with deionized water, each time using three times the mass of the composite precursor filter cake, to remove water-soluble sodium salts and nitrates from the precipitated slurry. The washed composite precursor filter cake was dried at 110°C for 12 hours to obtain a dried precursor. The dried precursor was placed in an air atmosphere and heated from an indoor environment to 500°C at a rate of 3°C / min. It was maintained at 500°C for 4 hours to obtain an oxidized catalyst precursor. The oxidized catalyst precursor was then tableted, crushed, and sieved. 1.0 g of 20-40 mesh particles was loaded into a fixed-bed reactor. An H2 gas flow rate of 80 mL / min was introduced, and the temperature was heated from an indoor environment to 300°C at a rate of 3°C / min. The reactor was then reduced in an H2 atmosphere at 300°C for 2 hours to obtain the catalyst for methanol synthesis. After reduction in an H2 atmosphere, the fixed-bed reactor was switched to a mixed feed gas of H2 and CO2, with a molar ratio of H2 to CO2 of 5.1. The reaction system was maintained at 270°C, a reaction pressure of 8.0 MPa, and a reaction space velocity of 5000 h⁻¹. -1 After the product flows through the condensation unit, the condensate is used for quantitative analysis of methanol, and the uncondensed gas is used for quantitative analysis of CO2, CO and unreacted H2. In this embodiment, the molar ratio of Cu, Zn, Al, Ce, Zr, and La is on the other side of the formulation range, while Ce, Zr, and La are still in the range of 5-8 parts, 3-5 parts, and 1-3 parts, respectively, forming a cerium-zirconium-lanthanum composite oxide composed of CeO2, ZrO2, and La2O3; CeO2, ZrO2, and La2O3 are located in the same region of origin of the composite particles as the copper-based active phase, forming an interfacial active region; In this embodiment, the reaction pressure of 8.0 MPa is used to represent the bed operating pressure of the fixed-bed reactor; this reaction pressure, together with 6.0 MPa in Example 1, reflects the fixed-bed application range of 6.0-8.0 MPa; this embodiment does not apply the carbon dioxide conversion rate, methanol selectivity and CO selectivity values ​​under the 6.0 MPa condition in Example 1. Example 4 A mixed nitrate solution was prepared based on the molar amounts of metal elements, with the molar ratio of Cu, Zn, Al, Ce, Zr, and La being 35:25:12:6:4:2. Specifically, Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Ce(NO3)3, ZrO(NO3)2, and La(NO3)3 were converted to the molar amounts of Cu (0.35 mol), Zn (0.25 mol), Al (0.12 mol), Ce (0.06 mol), Zr (0.04 mol), and La (0.02 mol) respectively, and then added to deionized water to prepare a mixed nitrate solution with a total molar concentration of 0.50 mol / L. Separately, Na2CO3 was added to deionized water to prepare a Na2CO3 solution with a concentration of 1.00 mol / L. Deionized water was added to the reactor as the base liquid, and the stirring speed was 500 r / min. The liquid phase in the reactor was maintained at 65°C. The mixed nitrate solution and Na2CO3 solution were added dropwise to the reactor in a co-current manner. The flow rate of the Na2CO3 solution was adjusted according to the pH of the liquid phase in the reactor to maintain the pH of the liquid phase in the reactor at 7.5. After all the mixed nitrate solution was added, the pH of the liquid phase in the reactor was maintained at 7.5 for another 30 min to obtain the precipitated slurry. The precipitated slurry was aged in the mother liquor for 12 hours, during which the liquid phase in the reactor was maintained at 65°C. After aging, the mixture was filtered to obtain a composite precursor filter cake. The composite precursor filter cake was washed five times with deionized water, each time using three times the mass of the composite precursor filter cake. The washed composite precursor filter cake was dried at 110°C for 12 hours, and then heated from indoor environment to 500°C in air at a rate of 3°C / min, and held at 500°C for 4 hours to obtain an oxidized catalyst precursor. The oxidized catalyst precursor was tableted, crushed, and sieved. 1.0 g of 20-40 mesh particles was then loaded into a fixed-bed reactor. The fixed-bed reactor was first purged with an H2 gas flow rate of 80 mL / min, and reduction was carried out at 300℃ for 2 h. Subsequently, without removing the catalyst, the atmosphere in the fixed-bed reactor was directly switched to a mixed feed gas of H2 and CO2, with a molar ratio of H2 to CO2 of 5.1. The reaction system was maintained at 270℃, a reaction pressure of 6.0 MPa, and a reaction space velocity of 5000 h⁻¹. -1 The exported products were separated into condensate and uncondensed gas, and then quantitatively analyzed separately. In this embodiment, the oxidized catalyst precursor is reduced in a fixed-bed reactor under H2 atmosphere. CuO is reduced to form a copper-based active phase, while ZnO, Al2O3, and cerium-zirconium-lanthanum composite oxide are retained as oxide structures. The cerium-zirconium-lanthanum composite oxide is located around the copper-based active phase. This process enables the formation of an interfacial active region within the same particle, in which the copper-based active phase, zinc-aluminum oxide framework, and cerium-zirconium-lanthanum composite oxide all participate. In this embodiment, the carbon dioxide adsorption activation region, the carbon-containing intermediate hydrogenation conversion region, the copper-based active phase migration restriction region, and the surface acidity / basicity adjustment region all originate from the same composite precursor particle, rather than being formed by external mixing of different powders; this setting is used to illustrate the structural relationship between the in-situ formed cerium-zirconium-lanthanum composite oxide and the copper-based active phase. Comparative Example 1 A mixed nitrate solution containing Cu(NO3)2, Zn(NO3)2, and Al(NO3)3 was prepared according to a molar ratio of Cu, Zn, and Al of 35:25:12, without adding Ce(NO3)3, ZrO(NO3)2, and La(NO3)3; the total molar concentration of metal elements in the mixed nitrate solution was 0.50 mol / L; separately, Na2CO3 was added to deionized water to prepare a Na2CO3 solution with a concentration of 1.00 mol / L. A mixed nitrate solution and a Na₂CO₃ solution were added dropwise to a reactor in a co-current manner. The liquid phase in the reactor was maintained at 65°C, the stirring speed was 500 r / min, and the pH of the liquid phase in the reactor was maintained at 7.5. After all the mixed nitrate solution was added, the pH of the liquid phase in the reactor was maintained at 7.5 for another 30 min to obtain a precipitate slurry. The precipitate slurry was aged in the mother liquor for 12 h, filtered, washed five times with deionized water, dried at 110°C for 12 h, and calcined at 500°C in air for 4 h to obtain a Cu-Zn-Al oxidized catalyst precursor. This precursor was tableted, crushed, and sieved into 20-40 mesh particles before being loaded into a fixed-bed reactor and reduced at 300°C in H₂ atmosphere for 2 h. This comparative example retains the CuO-ZnO-Al2O3 matrix, co-precipitation, aging, washing, drying, calcination and H2 atmosphere reduction process, omitting the Ce, Zr and La components; the resulting catalyst can form a copper-based active phase and a zinc-aluminum oxide framework, but does not have the cerium-zirconium-lanthanum composite oxide formed by CeO2, ZrO2 and La2O3. This comparative example does not contain the regions where CeO2, ZrO2, and La2O3 are located. Therefore, the carbon dioxide adsorption activation region, the copper-based active phase migration restriction region, and the surface acid-base regulation region cannot be represented by the cerium-zirconium-lanthanum composite oxide. This comparative example is used to demonstrate the structural differences between the cerium-zirconium-lanthanum composite oxide and the pure Cu-Zn-Al system. Comparative Example 2 A mixed nitrate solution containing Cu(NO3)2, Zn(NO3)2, Al(NO3)3, and Ce(NO3)3 was prepared according to a molar ratio of Cu, Zn, Al, and Ce of 35:25:12:6, without adding ZrO(NO3)2 and La(NO3)3; the total molar concentration of metal elements in the mixed nitrate solution was 0.50 mol / L; separately, Na2CO3 was added to deionized water to prepare a Na2CO3 solution with a concentration of 1.00 mol / L. A mixed nitrate solution and a Na2CO3 solution were added dropwise to a reactor in a co-current manner. The liquid phase in the reactor was maintained at 65°C, the stirring speed was 500 r / min, and the pH of the liquid phase in the reactor was maintained at 7.5. After all the mixed nitrate solution was added, the pH of the liquid phase in the reactor was maintained at 7.5 for another 30 min to obtain a precipitate slurry. The precipitate slurry was aged in the mother liquor for 12 h, then filtered, washed five times with deionized water, dried at 110°C for 12 h, and calcined at 500°C in air for 4 h to obtain an oxidized catalyst precursor containing a CeO2 dispersed phase. This precursor was tableted, crushed, and sieved into 20-40 mesh particles, and then reduced in a fixed-bed reactor at 300°C in an H2 atmosphere for 2 h. This comparative example retains the formation process of the CeO2 region, omitting the formation sources of ZrO2 and La2O3; the obtained catalyst does not contain the ZrO2 region and the La2O3 region, therefore the copper-based active phase migration restriction region and the surface acid-base regulation region cannot be taken over by the cerium-zirconium-lanthanum composite oxide. This comparative example is used to illustrate the difference between single cerium doping and cerium-zirconium-lanthanum composite oxides; single cerium doping only corresponds to the formation of carbon dioxide adsorption activation sites and cannot constitute a composite regulatory unit formed by CeO2, ZrO2 and La2O3 according to the functional division of labor of carbon dioxide adsorption activation, copper-based active phase stabilization and methanol selective regulation. Comparative Example 3 A mixed nitrate solution containing Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Ce(NO3)3, and ZrO(NO3)2 was prepared according to the molar ratio of Cu, Zn, Al, Ce, and Zr of 35:25:12:6:4, without adding La(NO3)3; the total molar concentration of metal elements in the mixed nitrate solution was 0.50 mol / L; separately, Na2CO3 was added to deionized water to prepare a Na2CO3 solution with a concentration of 1.00 mol / L. A mixed nitrate solution and a Na2CO3 solution were added dropwise to a reactor in a co-current manner. The liquid phase in the reactor was maintained at 65°C, the stirring speed was 500 r / min, and the pH of the liquid phase in the reactor was maintained at 7.5. After all the mixed nitrate solution was added, the pH of the liquid phase in the reactor was maintained at 7.5 for another 30 min to obtain a precipitate slurry. The precipitate slurry was aged in the mother liquor for 12 h, then filtered, washed five times with deionized water, dried at 110°C for 12 h, and calcined at 500°C in air for 4 h to obtain an oxidized catalyst precursor containing CeO2 and ZrO2 dispersed phases. This precursor was tableted, crushed, and sieved into 20-40 mesh particles, and then reduced in a fixed-bed reactor at 300°C in an H2 atmosphere for 2 h. This comparative example retains CeO2 and ZrO2, omitting La2O3; the resulting catalyst has a carbon dioxide adsorption activation region and a copper-based active phase migration restriction region, but there is no surface acidity / basicity regulation region undertaken by the region where La2O3 is located. This comparative example uses the same co-precipitation, aging, drying, calcination and H2 atmosphere reduction process as Example 1. The difference lies in the fact that La(NO3)3 was not added to the mixed nitrate solution; this setting is used to demonstrate the compositional significance of La2O3 in the cerium-zirconium-lanthanum composite oxide. Comparative Example 4 First, a mixed nitrate solution containing Cu(NO3)2, Zn(NO3)2, and Al(NO3)3 was prepared according to a molar ratio of Cu, Zn, and Al of 35:25:12, without adding Ce(NO3)3, ZrO(NO3)2, and La(NO3)3. The mixed nitrate solution and Na2CO3 solution were added dropwise to a reactor in a parallel flow. The liquid phase in the reactor was maintained at 65°C, the stirring speed was 500 r / min, and the pH of the liquid phase in the reactor was maintained at 7.5. After all the mixed nitrate solution was added, the pH was maintained at 7.5 for another 30 min to obtain a precipitate slurry. The precipitate slurry was aged in the mother liquor for 12 h, then filtered, washed 5 times with deionized water, dried at 110°C for 12 h, and calcined at 500°C in air for 4 h to obtain the CuO-ZnO-Al2O3 precursor. Separately, CeO2 powder, ZrO2 powder, and La2O3 powder were taken and, after conversion according to the molar ratio of Ce, Zr, and La metal elements of 6:4:2, were mixed with CuO-ZnO-Al2O3 precursor to make the molar ratio of Cu, Zn, Al, Ce, Zr, and La metal elements in the mixture 35:25:12:6:4:2; the mixture was then pressed into tablets, crushed, and sieved into 20-40 mesh particles, loaded into a fixed-bed reactor, and reduced at 300℃ for 2 hours in a H2 atmosphere. This comparative example retains the nominal molar ratios of Cu, Zn, Al, Ce, Zr, and La, but CeO2, ZrO2, and La2O3 are not formed by Ce(NO3)3, ZrO(NO3)2, and La(NO3)3 being added together with Cu(NO3)2, Zn(NO3)2, and Al(NO3)3 in the same mixed nitrate solution, nor by co-precipitation and calcination under the action of Na2CO3 solution; This comparative example is used to illustrate the difference between "the presence of components" and "the in-situ formed oxide dispersion phase". Although the post-mixing method has CeO2, ZrO2 and La2O3 powders, the carbon dioxide adsorption activation region, the carbon-containing intermediate hydrogenation conversion region, the copper-based active phase migration restriction region and the surface acidity and alkalinity adjustment region are not undertaken by the same composite precursor particles, so the interfacial active region structure in the examples cannot be formed.

[0019] Table 1

[0020] Table 2

[0021] Table 3

[0022] It should be further explained that Table 1 is used to record the differences in composition and preparation stages of different samples. Its core function is to limit the variables between the examples and comparative examples to the molar ratio of metal elements, the introduction method of Ce / Zr / La, precipitation conditions, and formation characteristics. In the table, "Cu:Zn:Al:Ce:Zr:La" represents the ratio of each element after conversion according to the molar amount of metal elements, not the molecular weight ratio of nitrates. "Total metal concentration" represents the concentration of the sum of the molar amounts of Cu, Zn, Al, Ce, Zr, and La metal elements in the mixed nitrate solution relative to the solution volume. "Na2CO3 concentration" represents the molar concentration of the precipitant solution. "pH" and "liquid phase" represent the control conditions of the liquid phase in the reactor during the co-precipitation process. The significance of Table 1 is to illustrate that: Examples 1 to 3 cover the formulation range of Cu, Zn, Al, Ce, Zr, and La; Example 4 demonstrates the reduction of the oxidized catalyst precursor in a fixed bed under H2 atmosphere; Comparative Example 1 omits Ce, Zr, and La; Comparative Example 2 retains only Ce; Comparative Example 3 omits La; and Comparative Example 4, although retaining the nominal ratio of 35:25:12:6:4:2, adds CeO2, ZrO2, and La2O3 as powders in a post-mixing manner. This allows us to distinguish the structural differences between "the presence of Ce, Zr, and La elements" and "Ce, Zr, and La co-precipitate in the same liquid phase in the form of precursors and form an in-situ dispersed phase after calcination," thus supporting the formation mechanism of the interfacial active zone. Table 2 records the reduction conditions, reaction conditions, and inlet and outlet carbonaceous flow rates in the fixed-bed reactor for Example 1. The "Catalyst Loading Amount" in the table represents the mass of 20-40 mesh catalyst particles entering the fixed-bed reactor. "H2 Reduction Conditions" and "H2 Flow Rate" describe how the oxidized catalyst precursor is reduced in the fixed bed under H2 atmosphere, converting CuO into a copper-based active phase. "Inlet CO2 Flow Rate" and "Inlet H2 Flow Rate" represent the molar flow rates at the reactor inlet. The inlet H2 flow rate is obtained by multiplying the inlet CO2 flow rate by the molar ratio of H2 to CO2, which is 5.1. In Table 2, the outlet CO2 and CO are obtained from the gas chromatography quantification of uncondensed gas, and the outlet CH3OH is obtained from the gas chromatography quantification of condensate. "Other carbonaceous matter flow rates" represents the total outlet carbonaceous matter flow rates other than CO2, CH3OH, and CO, which is used for carbon budget accounting and does not replace the separate calculation of methanol selectivity or CO selectivity. The purpose of this table is to list the inlet data, outlet data, and detection sources required for the final results separately, so that the calculation of carbon dioxide conversion rate, methanol selectivity, and CO selectivity all have a source of preliminary data. Table 3 is used to convert the inlet and outlet flow rates in Table 2 into reaction results; "CO2 flow rate participating in the reaction" in the table represents the difference between the inlet CO2 flow rate and the outlet unreacted CO2 flow rate, i.e., 100.00 mmol / h minus 2.80 mmol / h, resulting in 97.20 mmol / h; "Carbon dioxide conversion rate" represents the percentage of CO2 flow rate participating in the reaction relative to the inlet CO2 flow rate; "Methanol selectivity" represents the percentage of the outlet methanol molar flow rate relative to the CO2 molar flow rate participating in the reaction; "CO selectivity" represents the percentage of the outlet CO molar flow rate relative to the CO2 molar flow rate participating in the reaction. The "Carbon Balance" in Table 3 is used to calculate the correspondence between the inlet CO2 carbon molar quantity and the outlet CO2, CH3OH, CO and other carbon-containing substances carbon molar quantities. The outlet CO2 is 2.80 mmol / h, methanol is 91.47 mmol / h, CO is 3.40 mmol / h, and other carbon-containing substances are 2.33 mmol / h, totaling 100.00 mmol / h, corresponding to the inlet CO2 flow rate. This table is used to explain the results of 97.2%, 94.1%, and 3.5%, all of which are obtained by converting the fixed bed inlet flow rate, outlet condensate detection, uncondensed gas detection, and the original flow rate data in the carbon balance calculation.

[0023] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A catalyst for synthesizing methanol, characterized in that, include: For the hydrogenation of carbon dioxide to methanol, the catalyst comprises a CuO-ZnO-Al2O3 matrix and a cerium-zirconium-lanthanum composite oxide dispersed in the CuO-ZnO-Al2O3 matrix; the cerium-zirconium-lanthanum composite oxide comprises CeO2, ZrO2 and La2O3. Based on the molar amounts of metal elements, the molar ratio of Cu, Zn, Al, Ce, Zr, and La is (30-40):(20-30):(10-15):(5-8):(3-5):(1-3). After reduction in an H2 atmosphere, a copper-based active phase is formed in the CuO-ZnO-Al2O3 matrix, and an interfacial active region is formed between the cerium-zirconium-lanthanum composite oxide and the copper-based active phase for carbon dioxide adsorption activation, hydrogenation conversion of carbon-containing intermediates, and selective adjustment of methanol.

2. The catalyst for synthesizing methanol according to claim 1, characterized in that, Based on the molar amounts of the metallic elements, the molar ratio of Cu, Zn, Al, Ce, Zr, and La is 35:25:12:6:4:2, and the molar ratio of Ce, Zr, and La is 3:2:

1.

3. The catalyst for synthesizing methanol according to claim 1, characterized in that, The cerium-zirconium-lanthanum composite oxide is formed by co-precipitating and calcining Ce(NO3)3, ZrO(NO3)2 and La(NO3)3 with Cu(NO3)2, Zn(NO3)2 and Al(NO3)3 in the same mixed nitrate solution, and then co-precipitating and calcining in the presence of Na2CO3 solution. CeO2, ZrO2 and La2O3 are all in-situ formed oxide dispersions. Based on the molar parts of metallic elements, Ce is 5-8 parts, Zr is 3-5 parts, and La is 1-3 parts; CeO2 is used to form carbon dioxide adsorption activation sites, ZrO2 is used to form a copper-based active phase stable interface, and La2O3 is used to form surface acidity and alkalinity adjustment sites, so that the cerium-zirconium-lanthanum composite oxides are configured into composite control units according to the functional division of carbon dioxide adsorption activation, copper-based active phase stabilization and methanol selective regulation.

4. The catalyst for synthesizing methanol according to claim 1, characterized in that, The interfacial active region is a composite region formed by the same precipitated particles after drying, calcination and reduction in H2 atmosphere. The composite region simultaneously includes a copper-based active phase formed by the reduction of CuO in H2 atmosphere, a zinc-aluminum oxide framework formed by ZnO and Al2O3, and a cerium-zirconium-lanthanum composite oxide formed by CeO2, ZrO2 and La2O3. Within the interfacial active region, the CeO2 region serves as the carbon dioxide adsorption activation region, the copper-based active phase region serves as the carbon-containing intermediate hydrogenation conversion region, the ZrO2 region serves as the copper-based active phase migration restriction region, and the La2O3 region serves as the surface acidity / alkalinity adjustment region. The carbon dioxide adsorption activation region, the carbon-containing intermediate hydrogenation conversion region, the copper-based active phase migration restriction region, and the surface acidity / alkalinity adjustment region are all supported by composite precursor particles formed by co-precipitation.

5. A method for preparing a catalyst for synthesizing methanol, characterized in that, The catalyst for preparing the synthetic methanol according to any one of claims 1-4 comprises: S1. Prepare a mixed nitrate solution containing Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Ce(NO3)3, ZrO(NO3)2 and La(NO3)3 according to the molar ratio of Cu, Zn, Al, Ce, Zr and La as (30-40):(20-30):(10-15):(5-8):(3-5):(1-3); S2. The mixed nitrate solution and Na2CO3 solution are added dropwise into the reactor in a co-current manner. Co-precipitation is carried out under the conditions of pH 7-8 and liquid phase temperature of 60-70℃ in the reactor to obtain a precipitate slurry containing Cu, Zn, Al, Ce, Zr and La precursors. S3. After aging the precipitated slurry for 12 hours, filter and wash it to obtain the composite precursor filter cake. S4. The composite precursor filter cake is dried at 110°C and then calcined at 500°C for 4 hours to obtain the oxidized catalyst precursor. S5. The oxidized catalyst precursor is reduced in H2 atmosphere at 300℃ for 2h to obtain the catalyst for methanol synthesis.

6. The method for preparing a catalyst for methanol synthesis according to claim 5, characterized in that, In S2, a mixed nitrate solution and a Na2CO3 solution are added to the reactor in a parallel flow manner. The pH of the liquid phase in the reactor is maintained at 7.5, and the temperature of the liquid phase in the reactor is maintained at 65°C, so that the precursors of Cu, Zn, Al, Ce, Zr, and La are generated simultaneously in the same liquid phase environment and enter the same precipitate slurry.

7. The method for preparing a catalyst for synthesizing methanol according to claim 5, characterized in that, In S3, the precipitated slurry is aged for 12 hours, which allows the matrix precursor containing Cu, Zn, and Al and the composite oxide precursor containing Ce, Zr, and La to rearrange and distribute within the same precipitate particles. After washing to remove water-soluble sodium salts and nitrates from the precipitated slurry, a composite precursor filter cake is obtained.

8. The method for preparing a catalyst for methanol synthesis according to claim 5, characterized in that, In S4 and S5, calcination at 500℃ is used to convert the composite precursor filter cake into an oxidized catalyst precursor containing a CuO-ZnO-Al2O3 matrix and CeO2, ZrO2 and La2O3 composite oxides. Reduction at 300℃ in H2 atmosphere is used to reduce CuO to form a copper-based active phase and retain the cerium-zirconium-lanthanum composite oxide around the copper-based active phase.

9. The application of a catalyst for the synthesis of methanol, characterized in that, The catalyst for synthesizing methanol according to any one of claims 1-4 is used in a fixed-bed reactor for the hydrogenation of carbon dioxide to methanol reaction, wherein the reaction feedstock includes H2 and CO2, the molar ratio of H2 to CO2 is 5.1, the reaction system is at 270°C, and the reaction pressure is 6.0-8.0 MPa.

10. The application of the catalyst for methanol synthesis according to claim 9, characterized in that, The reaction pressure in the fixed-bed reactor is 6.0 MPa, and the reaction space velocity is 5000 h⁻¹. -1 The reaction system was set at 270℃, with a molar ratio of H2 to CO2 of 5.1 and a reaction space velocity of 5000 h⁻¹. -1 Under these conditions, the carbon dioxide conversion rate was 97.2%, the methanol selectivity was 94.1%, and the CO selectivity was 3.5%.